HUBUNGAN PENGETAHUAN MENGENAI MAKANAN CEPAT SAJI (FAST FOOD) DENGAN PERILAKU KONSUMSI MAKANAN CEPAT SAJI (FAST FOOD) PADA SISWA SEKOLAH MENENGAH ATAS PEMBANGUNAN LABORATORIUM UNIVERSITAS NEGERI PADANG - TRIYANTI, VIVI; Syarif, Winerlis; Chair, Ira Meirina (Journal of Home Economics and Tourism, 2014)
The purpose of this study was to analyze the relationship between knowledge about fast food with fast food consumption behavior in high school students/SMA Pembangunan Laboratorium UNP . This research is a descriptive correlational nature . The population in this research was 685 people are students of class X , XI , and XII in SMA Pembangunan Laboratorium UNP . Based on the survey results revealed that students' knowledge about fast food achievement levels obtained by 59 % of respondents with a lower category . Student behavior in consuming fast food achievement levels obtained by 81 % of respondents with a high category . The magnitude of the correlation coefficient variable ( X ) and variable ( Y ) is 0.615 with the interpretation that the two variables are strongly correlated . The results showed that there is a positive and significant relationship between knowledge of fast food with fast food consumption behavior in SMA Pembangunan Laboratorium UNP. Keywords: knowledge, consumption behavior, fast food.